Trump : think like a billionaire : everything you need to know about success, real estate, and life - Trump, Donald, 1946-; McIver, Meredith (Ballantine Books, 2005)
The author describes the secrets of investing in real estate, offers advice on spending money like a billionaire, and includes a behind the scenes look at his television program "The Apprentice."